A Floristic Analysis of Vascular Plants by the Disturbance Type and Application of Ecological Restoration Strategies in the Baekdudaegan Protected Area of South Korea - Young-Soo Kim; Gyu-Il Han; Seong-Bin Kim; Min-Woo Lee; Se-Kyu Song; Sang-Geun Kim; Tae-Im Heo (Diversity)
This study evaluated the floristic characteristics and ecological conditions of disturbed sites within the Baekdudaegan Protected Area by analyzing species occurrence and ecological indices according to the region and disturbance type. A total of 515 vascular plant species were recorded, including rare species, alien species, and Korean endemic plants. To assess ecological patterns, the Naturalization Index (NI), Urbanization Index (UI), and Sørensen similarity index were applied. The results showed that Mt. Seoraksan, Mt. Deogyusan, and Mt. Taebaeksan had relatively high NI and UI values, while Mt. Jirisan showed a comparatively low UI value. Among disturbance types, the hiking trail (HT) type, located in a high-altitude area with limited accessibility, also recorded lower values. Floristic similarity with reference ecosystems was higher in Mt. Jirisan, Mt. Deogyusan, and Mt. Taebaeksan, whereas Mt. Seoraksan exhibited the lowest similarity. The overall similarity between disturbance types was low, and the composition of plant species varied across disturbance types. These results suggest that differences in disturbance intensity, driven by the disturbance type and topographic conditions, influences the floristic composition. The findings of this study can serve as baseline data for developing site-specific restoration strategies for disturbed sites in the future.